PENGGUNAAN KATA DAN ISTILAH BAHASA INGGRIS PADA RUBRIK OPINI SURAT KABAR KOMPAS - Susetyo*, Agus Milu (Belajar Bahasa, 2016)
Language as a mean of communication is used to transfer message from the speaker or writer to the listener or reader. Communication can be done in spoken or written language; one of which is through mass media. A part of mass media in Kompas which is used a tool to convey messages of entertainment, or others is called as rubric opini. In rubric opini, provides a feature in which anyone with any different backgrounds can communicate their argument, opinion, criticisms or even suggestions. The standard Bahasa Indonesia must be applied within this rubric, but in facts there is still a lot of borrowing terms used. The English terms which are used in the borrowing should not be applied here for Kompas is one of the reputable national mass media in Indonesia which should uphold the use of the standard Bahasa Indonesia in its features. Hence, this has aroused the writer to conduct this study. Documentation applied as the method of gathering the data by collecting the whole documents from rubric opini feature of Kompas during August 2011.The result of the study showed that there are some categories of the borrowing used in the rubric; (1) base words, (2) suffixes, (3) terms, (4) phrases, and (5) acronyms. Keywords: english, words, terms, opinion